Strategic management from Islamic perspective : text and cases - Fontaine , Rodrigue; Mohd. Israil, Khaliq Ahmad (John Wiley, 2013)
While strategic management is a cornerstone of any MBA or business program, it’s almost always taught from conventional theories and typically American case studies. This book takes those traditional theories and interprets them from an Islamic perspective using more international case studies.